The effects of high glucose on bone marrow stromal cell differentiation - Karhu, Iida (My University, 2024)
Bone is a living tissue that is constantly being built and rebuilt during lifetime. Mesenchymal stromal cells (MSCs) found in the bone marrow can differentiate into bone-forming osteoblasts and fat cells i.e., adipocytes. Type 2 diabetes (T2D) is a metabolic disease characterized by prolonged high blood sugar i.e., hyperglycemia, insulin resistance, and bone complications, such as bone fragility and osteoporosis. Previous studies found that glucose transporter protein 4 (GLUT4) regulates MSC differentiation and insulin-regulated GLUT4 function is impaired in type 2 diabetes with insulin resistance. GLUT4 regulates the expression of thioredoxin-interacting protein (TXNIP). The expression of TXNIP increases in hyperglycemia and negatively affects cellular oxidative stress. The aim of the work was to investigate the effect of silencing GLUT4 and TXNIP on the differentiation of MSCs in the physiological (5,5 mM glucose) and in the hyperglycemic environment (25 mM glucose). MSCs were isolated from rat bone marrow and GLUT4 or TXNIP were silenced using siRNA method. Differentiation into osteoblasts or adipocytes was analyzed by measuring the expression of genes characteristic to osteoblasts and adipocytes with qPCR. In addition, cell viability was measured using the AlamarBlue assay. The differentiation of GLUT4-silenced cells was directed more into adipocytes and at the same time the differentiation into osteoblasts decreased. The effect was stronger in the hyperglycemic environment. The differentiation of TXNIP-silenced cells into adipocytes decreased, but the expression of GLUT4 was increased, suggesting that TXNIP affects GLUT4 function. The viability of GLUT4-silenced cells was decreased, but TXNIP silencing didn’t have an effect on cell viability. GLUT4 activity is necessary for osteoblast differentiation and its deficiency promotes differentiation into adipocytes, and increase the expression of TXNIP. In further studies, it would be good to study the interaction between TXNIP and GLUT4 and its importance for osteoblast differentiation.
Keywords: MSC, Osteoblast, Adipocyte, T2D, hyperglycemia, GLUT4, TXNIP